Sur l’ultraconvergence de série de Dirichlet - Miškelevičius, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Мишкелявичюс. О сверхсходимости ряда Дирихле A. Miškelevičius. Dirichlė eilutės virškonvergavimo klausimu